Low and variable tumor reactivity of the intratumoral TCR repertoire in human cancers - Scheper, Wouter; Kelderman, Sander; Fanchi, Lorenzo F; Linnemann, Carsten; Bendle, Gavin; de Rooij, Marije A J; Hirt, Christian; Mezzadra, Riccardo; Slagter, Maarten; Dijkstra, Krijn; Kluin, Roelof J C; Snaebjornsson, Petur; et al. (Nature medicine, 2019)
Infiltration of human cancers by T cells is generally interpreted as a sign of immune recognition, and there is a growing effort to reactivate dysfunctional T cells at such tumor sites . However, these efforts only have value if the intratumoral T cell receptor (TCR) repertoire of such cells is intrinsically tumor reactive, and this has not been established in an unbiased manner for most human cancers. To address this issue, we analyzed the intrinsic tumor reactivity of the intratumoral TCR repertoire of CD8 T cells in ovarian and colorectal cancer-two tumor types for which T cell infiltrates form a positive prognostic marker . Data obtained demonstrate that a capacity to recognize autologous tumor is limited to approximately 10% of intratumoral CD8 T cells. Furthermore, in two of four patient samples tested, no tumor-reactive TCRs were identified, despite infiltration of their tumors by T cells. These data indicate that the intrinsic capacity of intratumoral T cells to recognize adjacent tumor tissue can be rare and variable, and suggest that clinical efforts to reactivate intratumoral T cells will benefit from approaches that simultaneously increase the quality of the intratumoral TCR repertoire.